Gender differences in Working Capital Management amongst Small Business Owners in Uganda - Orobia, Laura A. (Journal of Economics and Behavioral Studies, 2013)
The purpose of this study is to examine gender differences on the effect of individual attributes on working capital management amongst small business owners. Based on a sample of 360 owner-managers of small businesses in the central business district of Kampala, the results show as follows. There are significant gender differences in perceived usefulness and attitude. Secondly, males and females do not statistically differ in terms of impulsivity. Thirdly, perceived usefulness significantly influences working capital management for females but not males. Fourthly, attitude significantly influences working capital management for males but not females. Lastly, the effect of impulsivity on working capital management is stronger for females than males. However, paucity of studies on the input perspective of working capital management limited crossvalidation of the findings with previous research. Future studies should be conducted to confirm the results. At policy level, understanding gender differences on the effect of the identified driving forces should be of interest to practitioners and policy makers in their effort to enhance small business management through developing appropriate gendered policies. This study contributes to the dearth of evidence of working capital management literature by investigating the effect of individual attributes as opposed to the conventional financial ratios.